Adsorption of Pb (II) by Chitosan Resulted from Bakau Crab’s Shell (Scylla sp) Chitin Isolation - Indah Sanjaya; Leny Yuanita (Jurnal ILMU DASAR, 2007)
The aim of this research was to find the effect of interaction time on adsorption of Pb (II) by chitosan.The research was done in three stages: (i), the isolation of chitin from Bakau Crab’s Shell (Scylla sp); (ii), chitin deacetilation becomes chitosan; (iii), interaction of chitosan to Pb (II). Qualitative analysis was done by ninhidrin test, while quantitatively was carried out by infra red spectra. Langmuir Hinshelwood kinetica equation was applied to determine adsorption velocity of chitosan to Pb (II), and one way analysis of variance to determine the effect of interaction time to adsorption of Pb (II) (α = 5%). Interaction time was 10, 30, 50, 70, 90, 110, and 130 minutes. The results showed that: (a) deacetilation degree of chitin and chitosan were 35.94 and 65.28 % respectively, (b) ninhidrin test was resulting purple colour for chitosan, (c) period time of equilibrium to adsorp Pb (II) was 70 minutes. From Langmuir- Hinshelwood kinetica equation resulting that k1 = 0.0014 minutes-1 and K = 1189.6 M-1. Range of chitosan adsorption velocity to Pb (II) was 2977. 10-7 to 3.275. 10-7 mol/L minutes.